PROSIDING: SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA) - Fisip, Wulan (PROSIDING: SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA), 2018)
PROSIDING: SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA)